A Froneira de sangue : história e literatura nas representações da violência em Goiás na passagem dos séculos XIX ao XX - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
This paper intends to analyze the cultural representations of violence developed on the frontier of Goiás in the late nineteenth and twentieth century. To undertake this proposal, analysis has been made through literary representations of the frontier and accounts of Catulino Antonio Viegas life, an active policeman during the first republic. Therefore, the concepts utilized are that of North American frontier traditions and the methodological approach of micro history and literary analysis that seeks to understand how the dynamics of violence has smeared blood on the frontier of the frontier in Goiás.
Keywords: Fronteira; Violência; Goiás; Literatura; Frontier; Violence; Goiás; Literature; LETRAS::OUTRAS LITERATURAS VERNACULAS; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::HISTORIA